"Land Reforms in India: a Survey of Policy, Legislation and Implementation" - "Appu, P. S." (New Delhi, 1996)
A nationwide survey is provided of 3 important programmes of land reform undertaken in India since independence. At the time of independence, the Indian agrarian structure was plagued by a number of weaknesses which inhibited agricultural growth. The land policy adopted aimed at eradicating these weaknesses. The programmes included the Abolition of Intermediary Interests, Tenancy Reform, and Imposition of Ceilings on Agricultural Holdings in tandem with the redistribution of surplus land. The survey examines policy, legislation, implementation and results of each programme. The programmes of land reform implemented did not lead to a significant redistribution of land, nor to the removal of all the obstacles to increasing agricultural production. The Abolition of Intermediary Interests was accomplished with reasonable efficiency, but Tenancy Reform and Ceilings on Agricultural Holdings achieved very little. The most important reason for poor performance was the lack of political will. The continuing relevance, however, of land reforms is highlighted. Although land reforms could not play an effective role in bringing about social justice, some measures of land reform are nevertheless needed to promote fast agricultural growth; in particular, tenancy laws should be amended to permit the leasing out of land.
Keywords: Economics of Land & Energy